The Study of Smart Grid Knowledge Visualization Key Technologies - Zhaoyang Qu; Songlin Hou; Li Zhu; Jia Yan; Shaoqing Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
To solve the problems of knowledge visualization for smart grid, such as single manifestations, low-efficient use and not high model reuse rate, a general three-dimensional smart grid knowledge visualization model was presented in this paper. First, the construction method of grid device models based on knowledge-based reasoning was given. Then, the grid visual scene building method was proposed. This included rapid scene organization strategy, and exploration on the storage and re-use mechanism of three-dimensional visualization scene. Moreover, collision detection using swarm intelligence and bionic computing to solve its existing problems. Finally, The feasibility and practicality of the method was verified by a developed intelligent power virtual drill platform based on JME (JMonkeyEngine). DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3998